HUBUNGAN BUDAYA ORGANISASI, GAYA KEPEMIMPINAN AUTHENTIC KEPALA SEKOLAH, MOTIVASI BERPRESTASI DALAM MENINGKATKAN KINERJA GURU - Dewi, Julita; Marsithah, Iis; Rizki, Sari (Research and Development Journal of Education, 2024)
The objectives of this research are to determine: 1) the direct relationship between organizational culture and teacher performance; 2) the direct relationship between authentic leadership style and teacher performance; 3) the relationship between organizational culture, through achievement motivation, and teacher performance; 4) the relationship between authentic leadership style, through achievement motivation, and teacher performance; 5) the relationship between achievement motivation and teacher performance. This research uses descriptive analysis with quantitative analysis and data analysis through path analysis. The study will be conducted at junior high schools in Central Aceh Regency, including SMPN 4 Takengon, SMP IT Cendikia Takengon, and SMP IT Al-Azhar. Data collection in this study uses questionnaires, with data analyzed through Pearson's product-moment correlation and multiple linear regression analysis. The research results show that the direct relationship between organizational culture and teacher performance is 0.539 (53.9%), classified as moderate. The direct relationship between the school principal's authentic leadership and teacher performance is 0.403 (40.3%), also moderate. The moderator variable (achievement motivation) strengthens the relationship between organizational culture and teacher performance by 0.578 (57.8%), classified as moderate. Similarly, achievement motivation strengthens the relationship between the school principal's authentic leadership and teacher performance by 0.578 (57.8%), also moderate. Finally, the direct relationship between achievement motivation and teacher performance is 0.514 (51.4%), which is moderate.